Eubacterial SpoVG homologs constitute a new family of site-specific DNA-binding proteins. - Brandon L Jutras (Public Library of Science (PLoS), 2013)
A site-specific DNA-binding protein was purified from Borrelia burgdorferi cytoplasmic extracts, and determined to be a member of the highly conserved SpoVG family. This is the first time a function has been attributed to any of these ubiquitous bacterial proteins. Further investigations into SpoVG orthologues indicated that the Staphylococcus aureus protein also binds DNA, but interacts preferentially with a distinct nucleic acid sequence. Site-directed mutagenesis and domain swapping between the S. aureus and B. burgdorferi proteins identified that a 6-residue stretch of the SpoVG α-helix contributes to DNA sequence specificity. Two additional, highly conserved amino acid residues on an adjacent β-sheet are essential for DNA-binding, apparently by contacts with the DNA phosphate backbone. Results of these studies thus identified a novel family of bacterial DNA-binding proteins, developed a model of SpoVG-DNA interactions, and provide direction for future functional studies on these wide-spread proteins.